Escalas: the awareness of time and pain - Merino, Antonio (2023)
This article offers a brief overview of the notion of the consciousness of time and pain in César Vallejo’s Escalas. Through the evocation of the past (childhood, the family home, the memory of the mother), Vallejo contrasts and juxtaposes two dimensions of reality (time and space), a «happy there» (the dreamed and recreated reality of childhood) and a «prison here» (the space of prison), generating a new way of «being» in the world which, in turn, reveals the true magnitude of tragedy, as occurs, for example, in «Alféizar» and «Más allá de la vida y la muerte» («Beyond life and death»). It is in this dynamic that one can observe a materiality of the space that surrounds the characters in Escalas’ stories, as well as an awareness of the pain and alienation of the human being in an unjust and corrupt world.